2010
DOI: 10.1016/j.conbuildmat.2010.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Clay-based composite stabilized with natural polymer and fibre

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited.In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
132
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(146 citation statements)
references
References 26 publications
10
132
1
3
Order By: Relevance
“…The most important advances in rammed earth construction using the "tapial" technique have centred on increasing the density and loadbearing capacity of the earth either by improving the compaction process by replacing earth rammers with small mechanical compactors (in the case of new buildings), or by using hardeners, selecting specific kinds of materials and reinforcing them with natural or artificial fibres (10)(11). In the context of restoration, attention is focussed on in situ consolidation of such materials (12), based on the fact that clay-rich soils encountered while building roads or digging foundations must be stabilised and/or consolidated to prevent problems caused by changes in humidity.…”
Section: Introductionmentioning
confidence: 99%
“…The most important advances in rammed earth construction using the "tapial" technique have centred on increasing the density and loadbearing capacity of the earth either by improving the compaction process by replacing earth rammers with small mechanical compactors (in the case of new buildings), or by using hardeners, selecting specific kinds of materials and reinforcing them with natural or artificial fibres (10)(11). In the context of restoration, attention is focussed on in situ consolidation of such materials (12), based on the fact that clay-rich soils encountered while building roads or digging foundations must be stabilised and/or consolidated to prevent problems caused by changes in humidity.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the mechanical strength, impermeability and the durability of locally produced adobe, in general, small amounts of quicklime or natural fibres are added to the soil matrix [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The use of local natural fibres, especially in developing countries, is more beneficial for the population as fibres are locally available in abundance and their productions are of low cost and low consuming energy besides are not polluting.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, it was found that adding fibres to rammed earth or to composite soils either decreased the unconfined compressive strength (UCS) (Maniatidis and Walker, 2003;Schroeder et al, 2005) or gave a small increase at low-fibre contents (Bouhicha et al, 2005;Galán-Marín et al, 2010;Ghavami et al, 1999;Houben and Guillaud, 1994;Marandi et al, 2008). The effect of fibre content on UCS was possibly governed by the clay content of the soil; soils with larger clay contents responded to increased fibre content with a higher UCS, while more sandy soils showed a lower UCS with increased fibre content.…”
Section: Fibre Stabilisation In Rammed Earthmentioning
confidence: 99%